Prophylactic antibiotics in laparoscopic cholecystectomy: Reducing postoperative infection risk–A meta-analysis and trial sequential analysis - Shufeng Wang; Qing Gao; Xiaogang Qi; Lihua Hong; Hai Huang (Heliyon)
Background: The impact of prophylactic antibiotics on postoperative infection following laparoscopic cholecystectomy remains controversial. This meta-analysis and trial sequential analysis aims to assess the efficacy of prophylactic antibiotics in reducing the risk of postoperative infection following laparoscopic cholecystectomy. Methods: Multiple databases including PubMed, Cochrane Library, EMBASE, and Web of Science were systematically searched to identify relevant randomized controlled trials (RCTs) published from inception to January 23, 2024. This study analyzed endpoints such as infection complications (IC) and surgical site infections (SSI). RCTs comparing prophylactic antibiotics versus placebo or no treatment in patients undergoing laparoscopic cholecystectomy were included. Data extraction and meta-analysis were performed. Additionally, trial sequential analysis was conducted to assess the robustness of evidence in meta-analysis. Results: Thirty-six RCTs with 9386 patients were included. The IC and SSI in prophylactic antibiotics group were significantly lower [pooled log risk-ratio (log RR): 0.37, 95 % confidence interval (CI):(−0.60, −0.14), p = 0.0017; pooled log RR: 0.30, 95 % CI (−0.51, −0.09), p = 0.01]. Trial sequential analysis revealed relative risk reductions of 33.09 % for IC and 27.96 % for SSI. Trial sequential analysis suggesting that the current evidence is robust. Studies involving low-risk patients and those with acute cholecystitis inclusion did not demonstrate a clear advantage in SSI reduction with prophylactic antibiotics. Conclusion: Prophylactic antibiotics significantly reduces the risk of postoperative infection in patients undergoing laparoscopic cholecystectomy. Moreover, the lack of research on the impact of prophylactic antibiotics on postoperative infections in patients with acute cholecystitis undergoing laparoscopic cholecystectomy underscores the importance of further investigation.